2020
DOI: 10.3329/ajmbr.v6i3.49807
|View full text |Cite
|
Sign up to set email alerts
|

Management of dietary services at National Institute of Cancer Research and Hospital (NICRH), Bangladesh

Abstract: Patient meals are an integral part of hospital treatment and crucial to aid recovery. A cross-sectional study was conducted to determine the Management of Dietary Services at National Institute of Cancer Research and Hospital. The purpose of this study was to make provision for safe, clean, hygienic and nutritious diet for the indoor patient as per their caloric requirement. This study compiled from 1st January to 31st December 2017 and the sample size was 113(dietary personnel 9 and patients 104) and it was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…(10,11), the standard is falling below the expectation which was revealed in a study conducted in Bangladesh where only 7% out of 112 respondents were pleased with level of cleanliness in hospital (11). This study also revealed that inadequate sanity is due to lack of manpower which is supported by a study conducted in Bangladesh (12). Where respondents strongly agreed that this factor have linkage with cleanliness, which is also revealed by a study in a NHS UK13 which suggested that appearance of the environment is the most important factor which could be achieved by having enough manpower.…”
Section: Resultssupporting
confidence: 50%
“…(10,11), the standard is falling below the expectation which was revealed in a study conducted in Bangladesh where only 7% out of 112 respondents were pleased with level of cleanliness in hospital (11). This study also revealed that inadequate sanity is due to lack of manpower which is supported by a study conducted in Bangladesh (12). Where respondents strongly agreed that this factor have linkage with cleanliness, which is also revealed by a study in a NHS UK13 which suggested that appearance of the environment is the most important factor which could be achieved by having enough manpower.…”
Section: Resultssupporting
confidence: 50%
“…As found in previous studies in Jordan [31] and Iran [45], this current study indicated that participants from private hospitals had higher knowledge, attitudes and practices scores on food safety than those from government hospitals. Begum et al mentioned food service as one of the more emergent supporting services compared to other hospital services [23]. Usually, government hospitals have scarce funding, governance issues and a limited skilled workforce, although the Government of Bangladesh has been working hard to fill the gaps in the national healthcare system [23,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Begum et al mentioned food service as one of the more emergent supporting services compared to other hospital services [23]. Usually, government hospitals have scarce funding, governance issues and a limited skilled workforce, although the Government of Bangladesh has been working hard to fill the gaps in the national healthcare system [23,[46][47][48]. Another possible reason could be that most of the well-established private hospitals are located in the capital and divisional cities of Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overcrowding and limited facilities like handwashing stations in Bangladeshi healthcare settings add to the challenges [ 30 ]. A study at a cancer research facility found low patient satisfaction with meals, indicating the need for improvement [ 31 ]. Inadequate monitoring and funding in healthcare facilities contribute to illnesses among hospital workers and caregivers [ 30 ].…”
Section: Introductionmentioning
confidence: 99%